Oncofetal HMGA2 effectively curbs unconstrained (+) and (−) DNA supercoiling - Zhao, Xiaodan (2018)
HMGA2 belongs to the family of the high mobility group (HMG) proteins. It binds DNA via three AT-hook domains to the minor groove of adenine-thymine (AT) rich DNA. Recently, a new function of HMGA2 as a replication fork chaperone that protects stem and cancer cells from replication fork collapse induced by chemotherapeutic agents was uncovered, suggesting a previously uncharacterized binding at replication forks. In this study, we examined HMGA2 binding to four DNA structures relevant to replication forks, namely ds DNA, ss DNA, forked DNA and supercoiled DNA plectonemes. We detected HMGA2 binding to supercoiled DNA at the lowest concentration and this binding mode transiently stabilizes the supercoiled plectonemes against relaxation by type I topoisomerase. Together, these findings suggest a plausible mechanism how fork regression and collapse are attenuated by HMGA2 during replication stress, i.e. through transient stabilization of positively supercoiled plectonemes in the parental duplex.